2007
DOI: 10.1002/nau.20420
|View full text |Cite
|
Sign up to set email alerts
|

β3‐Adrenoceptors in urinary bladder

Abstract: The beta-adrenoceptor (AR) is currently classified into beta(1), beta(2), and beta(3) subtypes. A third subtype, beta(3)-AR, was first identified in adipose tissue, but has also been identified in smooth muscle tissue, particularly in the gastrointestinal tract and urinary bladder smooth muscle. There is a predominant expression of beta(3)-AR messenger RNA (mRNA) in human bladder, with 97% of total beta-AR mRNA being represented by the beta(3)-AR subtype and only 1.5 and 1.4% by the beta(1)-AR and beta (2)-AR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 69 publications
4
108
1
3
Order By: Relevance
“…␤ 3 AR agonists also relaxed rat bladder smooth muscle strips (Fujimura et al, 1999;Longhurst and Levendusky, 1999;Woods et al, 2001;Takeda et al, 2003). Relaxation of rat detrusor can be mediated by all ␤ARs (Yamaguchi and Chapple, 2007). In tissues where ␤ 2 ARs and ␤ 3 ARs are coexpressed, the ␤ 2 /␤ 3 receptor heterodimer can mediate unique signals (Breit et al, 2004).…”
Section: ϫ12mentioning
confidence: 97%
See 2 more Smart Citations
“…␤ 3 AR agonists also relaxed rat bladder smooth muscle strips (Fujimura et al, 1999;Longhurst and Levendusky, 1999;Woods et al, 2001;Takeda et al, 2003). Relaxation of rat detrusor can be mediated by all ␤ARs (Yamaguchi and Chapple, 2007). In tissues where ␤ 2 ARs and ␤ 3 ARs are coexpressed, the ␤ 2 /␤ 3 receptor heterodimer can mediate unique signals (Breit et al, 2004).…”
Section: ϫ12mentioning
confidence: 97%
“…Three subtypes of ␤ARs, ␤ 1 AR, ␤ 2 AR, and ␤ 3 AR, are expressed in bladder of several species, including human and rat (Yamaguchi and Chapple, 2007). ␤ 3 ARs, which are considered the predominant subtype in human bladder, are coupled to excitatory G s and inhibitory G i proteins (Vrydag and Michel, 2007).…”
Section: ϫ12mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that urothelial-derived NO can be released in response to mechanical as well as chemical stimulation and may either facilitate or inhibit the activity of bladder afferent nerves conveying bladder sensation (18,42). In this regard, activation of urothelial receptors and release of inhibitory mediators may explain, in part, the mechanism of action for therapies (e.g., ␤ 3 -AR agonists) in treatment of bladder disorders such as the overactive bladder (OAB) (137,283,301).…”
Section: Urothelium-lamina Propria Interactionsmentioning
confidence: 99%
“…The effective alternative class of agents to the antimuscarinics with proven efficacy and acceptable tolerability are the β 3 -adrenoceptor agonists (35). The detrusor muscle containing β -ARs and three subtypes ( β 1 , β 2 , and β 3 ) have been identified in most species (36,37).…”
Section: Pharmacotherapymentioning
confidence: 99%